High temperature gelling agent for oil and gas applications - Rasidi, Roslan; Jamil, Ismail; Mohd Hasbi, Ab. Rahim; Norhanis, Arbaa′In (2018)
Utilization of viscous fluid in a wellbore have been a common practice to enhance oil and gas hydrocarbons production. The viscous fluids are usually produced by hydrating common gelling agent such as hydroxyethyl cellulose, guar gum and xanthan gum in water or aqueous solution. As the oil exploration shifted towards higher-temperature reservoir, the common gelling agents are no longer usable because of degradation upon exposed to high temperature.